Achieving the UNAIDS first '95' in prenuptial HIV/AIDS testing among reproductive-aged Rwandese women: A multilevel analysis of 2019-20 population-based data - Michael Ekholuenetale; Olah Uloko Owobi; Amadou Barrow (Public Library of Science (PLoS), 2023)
A significant public health concern that disproportionately affects women is human immunodeficiency virus (HIV). Prenuptial HIV testing is no doubt a major step for people to learn their HIV status. In this study, the coverage of prenuptial HIV testing and its associated factors were examined among reproductive-aged Rwandese women. This study included a total of 14,634 reproductive-aged Rwandese women using 2019-20 Rwanda Demographic and Health Survey (RDHS). The coverage of prenuptial HIV/AIDS testing and the variables influencing it were evaluated using percentage and multilevel logit model. The level of significance was set at p<0.05. The weighted prevalence of prenuptial HIV/AIDS testing was 45.9% (95%CI: 44.8%-47.1%). The respondents who attained primary and secondary+ education had 31% (OR = 1.31; 95%CI: 1.09-1.59) and 56% (OR = 1.56; 95%CI: 1.25-1.95) higher odds of prenuptial HIV/AIDS testing, when compared with uneducated women. Those who got married or had their first sex at an adult age (18+ years), had higher odds of prenuptial HIV/AIDS testing, when compared with women who got married before age 18 years or never had sex respectively. Women's age, nativity and region were associated with prenuptial HIV testing. Women with knowledge of HIV test kits, had higher odds of prenuptial HIV/AIDS testing (OR = 1.45; 95%CI: 1.30-1.63), when compared with those with no knowledge of HIV test kits. The respondents from female-headed households had 12% reduction in prenuptial HIV/AIDS testing (OR = 0.88; 95%CI: 0.80-0.97), when compared with their male-headed counterparts. The moderately (OR = 1.16; 95%CI: 1.03-1.31) and highly (OR = 1.55; 95%CI: 1.37-1.75) enlightened women had higher odds of prenuptial HIV/AIDS testing, when compared with those with low enlightenment. The uptake of prenuptial HIV/AIDS testing was relatively low among Rwandese women. We recommend improving women's education, enlightenment, delay in sexual debut, marriage at adult age (18years) and increasing knowledge about HIV testing among women.